Edaphoclimatic and genetic influence on soil water availability factor for different sugarcane varieties. - ANJOS, J. C. R. dos (2023)
Sugarcane is grown in all Brazilian states; however, water stress is the main limiting factor of crop productivity in most farming environments (FEN). Thus, the objective was to verify the water availability factor in the soil (factor f) between FEN and sugarcane varieties. The assay was conducted in the Central and Southern Regions of Goiano, in Red Latosol with distinct physical-water attributes among the FEN.